Joint universality of Dirichlet L-functions and periodic Hurwitz zeta-functions - Janulis, Kęstutis; Laurinčikas, Antanas; Macaitienė, Renata; Šiaučiūnas, Darius (Mathematical Modelling and Analysis, 2012)
In the paper, we prove that every system of analytic functions can be approximated simultaneously uniformly on compact subsets of some region by a collection consisting of shifts of Dirichlet L-functions with pairwise non-equivalent characters and periodic Hurwitz zeta-functions with parameters algebraically independent over the field of rational numbers.